Electrochemical Characteristics and Transport Properties of V(II)/V(III) Redox Couple in a Deep Eutectic Solvent: Magnetic Field Effect - Cheng, Rong; Xu, Juncai; Wang, Xinyang; Ma, Qiang; Su, Huaneng; Yang, Weiwei; Xu, Qian (Frontiers in Chemistry, 2020)
Compared with conventional aqueous electrolytes, deep eutectic solvent (DES) has a wider electrochemical stability window, simple preparation, potential biodegradability, and lower cost, leading to its utilization as electrolyte for non-aqueous redox flow batteries (RFB). However, the large viscosity and inferior transport properties hinder the wide spread of DES electrolyte. To circumvent these issues, various additives as well as external fields can be applied separately or synergistically. This work reports a study on the inclusion of a DC magnetic field to the glycol-based DES electrolyte of a RFB. The effects of magnetic field on the physical and electrochemical characteristics of the electrolyte and the active redox couple on mass transfer are studied by cyclic voltammetry and electrochemical impedance spectroscopy. The experimental results show that the viscosity of the vanadium DES electrolyte decreases and the conductivity increases after adding a magnetic field. With the intensity of the added magnetic field increases, the oxidation and reduction peak current densities of the vanadium DES electrolyte keep increasing. Under the magnetic field intensity of 605 mT, the oxidation peak current density and the reduction peak current density increases 41.56 and 30.74%, respectively, compared with those of no added magnetic field. The ohmic resistance and electrochemical reaction resistance of the vanadium DES electrolyte are reduced when adding the magnetic field, reaching to 40.55 and 43.28%, respectively, with a magnetic field intensity of 605 mT. This study shows an effective yet simple way to improve the physical and electrochemical properties of DES electrolyte, which owns the potential to be widely applied in non-aqueous redox flow batteries.